Pemberian Abon Belut (Monopterus albus) terhadap Asupan Protein, Fe dan Kadar Hemoglobin Penderita TB Paru - Oslida Martony; Riris Oppusunggu (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effect of giving shredded eel on the intake of protein, Fe and hemoglobin levels of patients with pulmonary tuberculosis. The method used is a quasi-experimental design with one group pre and post-test design. The research sample was taken using a total sampling technique. The results showed that the average intake of protein, Fe and Hb levels after administration of shredded eel obtained a p-value of 0.000 and the significance value of each intake level was 0.000, 0.000, 0.001. In conclusion, there is a significant effect between the provision of shredded eel on the intake of protein, Fe and hemoglobin levels in patients with pulmonary TB. Keywords: Shredded Eel, Fe, Hemoglobin, Protein